1995
DOI: 10.1073/pnas.92.26.12041
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the inducible form of nitric oxide synthase in the brains of patients with multiple sclerosis.

Abstract: Nitric oxide (NO) has been implicated as a pathogenic mediator in a variety of central nervous system (CNS) We have reported (1) that Borna disease virus, rabies virus, and herpes simplex virus induce the increased expression of inducible nitric oxide synthase (iNOS) mRNA in the brains of intrathecally infected mice and rats. We and others (2) also found that the induction of experimental allergic encephalomyelitis resulted in a similar increase in iNOS mRNA expression, suggesting that a similar phenomenon m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
234
1
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 441 publications
(254 citation statements)
references
References 30 publications
16
234
1
3
Order By: Relevance
“…In the wide variety of immune-mediated mechanisms and molecules that could potentially cause CNS tissue damage in MS, many results point to the pathogenetic significance of nitric oxide (NO) (2)(3)(4). Several studies have shown that NO is produced in excess in the CNS (5)(6)(7) and NO metabolites are increased in body fluids of patients with MS (8)(9)(10). The toxicity of NO is significantly enhanced when it combines with superoxide to rapidly form the peroxynitrite anion (11).…”
Section: Introductionmentioning
confidence: 99%
“…In the wide variety of immune-mediated mechanisms and molecules that could potentially cause CNS tissue damage in MS, many results point to the pathogenetic significance of nitric oxide (NO) (2)(3)(4). Several studies have shown that NO is produced in excess in the CNS (5)(6)(7) and NO metabolites are increased in body fluids of patients with MS (8)(9)(10). The toxicity of NO is significantly enhanced when it combines with superoxide to rapidly form the peroxynitrite anion (11).…”
Section: Introductionmentioning
confidence: 99%
“…Two early reports that examined the expression of NADPH diaphorase staining as an indicator of NO production supported a role for astrocytes as a source of NO in MS lesions, 14,15 however, two subsequent studies using a reverse transcriptase in situ polymerase chain reaction (PCR) hybridization and/or immunocytochemical approach failed to detect iNOS in astrocytes, and instead implicated cells of the monocyte/macrophage lineage. 16,17 More recently, a study of brain biopsies from two acute cases of MS in young adults detected signal for iNOS in both reactive astrocytes and perivascular monocytes/macrophages, whereas no signal was found in more chronic MS cases. 18 These data suggest that the extent of lesion activity may critically affect which cell types express iNOS in the lesion.…”
mentioning
confidence: 99%
“…Nitrotyrosine has been detected in samples from a wide variety of disease states, including acute lung injury (1, 2), atherosclerosis (3,4), neurodegenerative diseases (5)(6)(7)(8), bacterial and viral infections (9 -11), aging (12), chronic inflammation (13), and exposure to cigarette smoke (14) or carbon monoxide (15). In most of the above cases, the nitrotyrosine detection was presumed to be the result of the reaction of tyrosine residues with peroxynitrite/ peroxynitrous acid.…”
mentioning
confidence: 99%